THE RELATIONSHIP BETWEEN MATHEMATICS ANXIETY OF SENIOR HIGH SCHOOL STUDENTS WITH MATHEMATICS LEARNING ACHIEVEMENT REVIEWED BASED ON GENDER - Nabilah, Jennie; Sutini, Sutini (Jurnal Pendidikan Matematika dan IPA, 2026)
This study investigates the relationship between mathematics anxiety and mathematics learning achievement, with attention to gender differences, in students at Sekolah Indonesia Kuala Lumpur. Eighteen students (8 males and 10 females) participated, with learning achievement measured using formative test results and mathematics anxiety assessed through a questionnaire. Depending on the normality of the data distribution, the t-test, Mann-Whitney U test, and Spearman correlation were applied in the analysis. Results showed that female students achieved higher academic performance and reported lower levels of mathematics anxiety compared to male students. For male students, mathematics anxiety was negatively correlated with achievement, whereas for female students, the correlation tended to be positive. These findings highlight the importance of addressing mathematics anxiety and adopting gender-sensitive teaching strategies in the learning process.